THU0438 Comparative study of infliximab versus adalimumab in refractory uveitis associated to cystoid macular oedemadue to behÇet's disease. mulcitenter study of 40 cases. (12th June 2018) - Atienza-Mateo, B.; Calvo-Río, V.; Martín-Varillas, J.L.; Demetrio-Pablo, R.; Beltrán, E.; Gandía, M.; Mesquida, M.; Adan, A.; Hernández, M.V.; Díaz, D.; Valls, E.; Martinez, L.; et al.
Abstract : Objectives: To compare the efficacy of infliximab (IFX) versus adalimumab (ADA) as first biologic drug in refractory uveitis with cystoid macular oedema (CME) associated to BD. Methods: Multicenter study of 40 patients with BD-associated uveitis with CME refractory or intolerant to standard treatment (corticosteroids and at least one conventional immunosuppressive agent). CME was considered if macular thickness was greater than 300 µm. Comparative outcome measures were macular thickness, improvement of visual acuity (VA), activity of anterior chamber inflammation and vitritis. Results were expressed as mean ±SD for variables with a normal distribution, or as median [25th-75th interquartile range- IQR] when not normally distributed. The comparison of continuous variables among time-periods was performed with the Wilcoxon signed rank test. Results: We selected patients with CME from a cohort of 177 patients with refractory BD-related uveitis (n=40). IFX was used in 15 cases and ADA in 25. No significant differences at baseline were observed between IFX vs ADA groups in sex (♂/♀ 8/7 vs 13/12, p=0.93), mean age (38±9 vs 41±10 years, p=0.53), HLA-B51 + (10 vs 19, p=0.87), uveitis pattern (panuveitis 67% vs 80%, posterior uveitis 33% vs 20%, p=0.34), previous conventional treatment (intravenous pulses of methylprednisolone 60% vs 52%, p=0.62, oral corticosteroids 93% vs 72%, p=0.1, methotrexate 53% vs 52%, p=0.93, cyclosporin A 73% vs 88%, p=0.23, azathioprine 53% vs 56%, p=0.86, other drugs 47% vs 68%, p=0.18), and combined treatment (67% vs 64%, p=0.86). After 1 year of therapy, ocular remission was achieved in 60% of cases with IFX and in 76% of cases with ADA (p=0.28). Regarding CME, 65% of patients with IFX reached a macular thickness <250 µm vs 87% of patients with ADA, with no statistically significant differences (p=0.07). Evolution of ocular parameters is shown in the table 1. Only 2 adverse effects were observed, both in ADA group (local rash and bacteremia). Conclusions: IFX and ADA show a similar efficacy in the treatment of CME in BD-related refractory uveitis. Reference: [1] Calvo-Río V, Blanco R, Beltran E, Sanchez-Burson J, Mesquida M, Adan A, et al. Anti-TNF- therapy in patients with refractory uveitis due to Behcet's disease: a 1-year follow-up study of 124 patients. Rheumatology (Oxford)2014;53(12):2223–31. Disclosure of Interest: None declared